2019
DOI: 10.3390/ijerph16244951
|View full text |Cite
|
Sign up to set email alerts
|

Testing Demands and Resources as Determinants of Vitality among Different Employment Contract Groups. A Study in 30 European Countries

Abstract: The aim of this study was to investigate the relative importance of four job demands and five job resources for employee vitality, i.e., work engagement and exhaustion, in three different employment groups: permanent, temporary and temporary agency workers. We employed data from the sixth European Working Conditions Survey (EWCS) collected in 2015 comprising 28,042 employees from 30 European countries. We used linear regression analyses and dominance analysis (DA). The results showed minor mean differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 57 publications
2
30
0
1
Order By: Relevance
“…Job autonomy was assessed with the item “In my job, I have the autonomy I need”; skill development, with the item “In my job, I have the opportunity to acquire knowledge and develop my skills”; and performance feedback, with the item “In my job, I am provided with constructive feedback on the quality of my work.” Participants responded using a 5-point rating scale, from 1 for “strongly disagree” to 5 for “strongly agree.” Job autonomy, skill development, and performance feedback have been considered important job resources in occupational health research (e.g., Schaufeli et al, 2009 ; Hakanen et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Job autonomy was assessed with the item “In my job, I have the autonomy I need”; skill development, with the item “In my job, I have the opportunity to acquire knowledge and develop my skills”; and performance feedback, with the item “In my job, I am provided with constructive feedback on the quality of my work.” Participants responded using a 5-point rating scale, from 1 for “strongly disagree” to 5 for “strongly agree.” Job autonomy, skill development, and performance feedback have been considered important job resources in occupational health research (e.g., Schaufeli et al, 2009 ; Hakanen et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…From an etiological standpoint, burnout has been considered a product of insurmountable job stress ( Maslach et al, 2001 ). There is evidence, for instance, that increases in job demands (e.g., workload) and decreases in job resources (e.g., job autonomy), which can give rise to unmanageable difficulties at work, predict burnout ( Schaufeli et al, 2009 ; Hakanen et al, 2019 ). A systematic review and meta-analysis of 25 prospective/case-control studies conducted by Aronsson et al (2017) concluded that job support and workplace justice were protective against burnout symptoms whereas high job demands, low job control, high workload, low job reward, and job insecurity fostered the development of burnout symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A study concerning restaurant temporary agency work in Finland responses is sufficient as the focus is on restaurants, not the whole hospitality industry. For example, European Working Conditions Survey (EWCS) collected responses of 28,042 employees from 30 European countries and got only 380 temporary agency workers to respond, and that was all industries combined (Hakanen, Ropponen, De Witte, & Schaufeli, 2019).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…This aspect of job resources results from the fact that they fulfill basic human needs for autonomy, competence, and relatedness [20]. Indeed, a recent dominance analysis of the data from the sixth European Working Conditions Survey showed that job resources explained 94%-95% of the variance observed in work engagement [21]. The abundance of job resources triggers a motivational process: through improved work engagement, job resources lead to positive outcomes, such as stronger organizational commitment and better work performance [16,19].…”
Section: Social Job Resourcesmentioning
confidence: 99%